Endochondral Bone Regeneration by Non-autologous Mesenchymal Stem Cells - Longoni, Alessia; Pennings, I.; Cuenca Lopera, Marta; van Rijen, M. H. P.; Peperzak, Victor; Rosenberg, A. J. W. P.; Levato, Riccardo; Gawlitta, Debby (Frontiers in Bioengineering and Biotechnology, 2020)
Mimicking endochondral bone formation is a promising strategy for bone regeneration. To become a successful therapy, the cell source is a crucial translational aspect. Typically, autologous cells are used. The use of non-autologous mesenchymal stromal cells (MSCs) represents an interesting alternative. Nevertheless, non-autologous, differentiated MSCs may trigger an undesired immune response, hampering bone regeneration. The aim of this study was to unravel the influence of the immune response on endochondral bone regeneration, when using xenogeneic (human) or allogeneic (Dark Agouti) MSCs. To this end, chondrogenically differentiated MSCs embedded in a collagen carrier were implanted in critical size femoral defects of immunocompetent Brown Norway rats. Control groups were included with syngeneic/autologous (Brown Norway) MSCs or a cell-free carrier. The amount of neo-bone formation was proportional to the degree of host-donor relatedness, as no full bridging of the defect was observed in the xenogeneic group whereas 2/8 and 7/7 bridges occurred in the allogeneic and the syngeneic group, respectively. One week post-implantation, the xenogeneic grafts were invaded by pro-inflammatory macrophages, T lymphocytes, which persisted after 12 weeks, and anti-human antibodies were developed. The immune response towards the allogeneic graft was comparable to the one evoked by the syngeneic implants, aside from an increased production of alloantibodies, which might be responsible for the more heterogeneous bone formation. Our results demonstrate for the first time the feasibility of using non-autologous MSC-derived chondrocytes to elicit endochondral bone regeneration in vivo. Nevertheless, the pronounced immune response and the limited bone formation observed in the xenogeneic group undermine the clinical relevance of this group. On the contrary, although further research on how to achieve robust bone formation with allogeneic cells is needed, they may represent an alternative to autologous transplantation.